Blockchain application - Loh, Kai Ying (2019)
Blockchain technology first emerged with the creation of Bitcoin in 2008 [1]. Since then, developers across the world have been trying to integrate blockchain in different areas, from banking and financial markets to Internet of Things (IoT). It has completely shaken the technology world with its potential. Some notable features are decentralization, immutability, and transparency [2].